2018
DOI: 10.1155/2018/2131895
|View full text |Cite
|
Sign up to set email alerts
|

Anacardium microcarpum Promotes Neuroprotection Dependently of AKT and ERK Phosphorylation but Does Not Prevent Mitochondrial Damage by 6‐OHDA

Abstract: Parkinson's disease is a degenerative and progressive illness characterized by the degeneration of dopaminergic neurons. 6-hydroxydopamine (6-OHDA) is a widespread model for induction of molecular and behavioral alterations similar to Parkinson and has contributed for testing of compounds with neuroprotective potential. The Brazilian plant Anacardium microcarpum is used in folk medicine for treatment of several illnesses; however, the knowledge about toxicology and biological effects for this plant is very rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…Our current experiments found that galangin significantly increased the viability of 6-OHDA-treated HT22 cells, which suggested that galangin could inhibit the degeneration or loss of neurons. The literature shows that 6-OHDA leads to mitochondrial damage, excessive generation of ROS, and the subsequent high expression of proapoptotic-related proteins [40,41]. Therefore, we further found that galangin had the capacity to inhibit ROS generation, apoptosis rate, and Bax/Bcl-2 in 6-OHDA-treated HT22 cells.…”
Section: Discussionsupporting
confidence: 53%
“…Our current experiments found that galangin significantly increased the viability of 6-OHDA-treated HT22 cells, which suggested that galangin could inhibit the degeneration or loss of neurons. The literature shows that 6-OHDA leads to mitochondrial damage, excessive generation of ROS, and the subsequent high expression of proapoptotic-related proteins [40,41]. Therefore, we further found that galangin had the capacity to inhibit ROS generation, apoptosis rate, and Bax/Bcl-2 in 6-OHDA-treated HT22 cells.…”
Section: Discussionsupporting
confidence: 53%